Lung bronchiectasisas a paradigm of the interplay between infection and colonization on plastic modulation of the pre-metastatic niche - Pisanu, Lucrezia; Mucaj, Klodjana; Conio, Valentina; Bertuccio, Francesco; Giana, Ilaria; Arlando, Lorenzo; Russo, Marianna; Montini, Simone; Bortolotto, Chandra; Corsico, Angelo Guido; Stella, Giulia Maria (Frontiers in Oncology, 2024)
The lungs are most often a preferential target organ for malignant spreading and growth. It is well known that chronic parenchymal inflammation and prolonged injuries represents an independent risk factor for cancer onset. Growing evidence supports the implication of lung microbiota in the pathogenesis of lung cancer. However, the full interplay between chronic inflammation, bacterial colonization, pathologic condition as bronchiectasis and malignant growth deserves better clarification. We here aim at presenting and analyzing original data and discussing the state-of-the-art on the knowledge regarding how this complex milieu acts on the plasticity of the lung pre-metastatic niche to point out the rationale for early diagnosis and therapeutic targeting.